The Influence of Darwinian Ideas on Greek Literary Writers of the Late Nineteenth and Early Twentieth Centuries: The Case of Emmanuel Roidis - Zarimis, Maria (The Historical Review/La Revue Historique, 2008)
Darwin’s works provoked an enormous response in many disciplines including the literary world. This paper presents a portion of my doctoral thesis3, which responds to a blind spot in Greek literary scholarship on evolutionary ideas in comparison to other Western countries. Little work to date focuses on modern Greek writers’s responses to Darwinian and other evolutionary ideas. This paper explores the impact of Darwin in selected writings of Emmanuel Roidis and how Roidis satirised Darwinism in his essays and short stories, contributing to the Darwinian discourse on "man’s place in nature" and by placing humanity on the same continuum as other primates. The year 2009 marks the 200th anniversary of Darwin’s birth and the 150th anniversary of the first publication of his The Origin of Species. It is timely, then, to consider Darwin’s impact on modern Greek literature.